2019
DOI: 10.1155/2019/8087462
|View full text |Cite
|
Sign up to set email alerts
|

Research on Shape Changes in Cylinder Electrodes Incident to Micro-EDM

Abstract: This paper discusses electrode wear changes under different operating conditions. A series of experiments were designed and conducted using an EDM machine tool with a rectangular pulse power supply. The phenomena of the cylinder electrode shape changes were abstracted from the experiments; the change mechanisms of the end face are discussed and verified by experimental data and interrelated theory. The results disclose that the shape of an electrode is subject to pulse-on time, discharge current density, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Only for negatively polarized tool electrodes, as in the present case, LI ET AL. revealed similar concave contours of the electrode tip and explained this fact with the skin effect and a decreased discharge probability in the center [87]. The authors did not attribute this concavity to the ejection of debris, but from their SEM images, it can be supposed that the center concavity deepened as a result of the increasing rotational speed [87] (p. 9).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Only for negatively polarized tool electrodes, as in the present case, LI ET AL. revealed similar concave contours of the electrode tip and explained this fact with the skin effect and a decreased discharge probability in the center [87]. The authors did not attribute this concavity to the ejection of debris, but from their SEM images, it can be supposed that the center concavity deepened as a result of the increasing rotational speed [87] (p. 9).…”
Section: Resultsmentioning
confidence: 93%
“…revealed similar concave contours of the electrode tip and explained this fact with the skin effect and a decreased discharge probability in the center [87]. The authors did not attribute this concavity to the ejection of debris, but from their SEM images, it can be supposed that the center concavity deepened as a result of the increasing rotational speed [87] (p. 9). It can therefore be further concluded that the concave tip contour was also a consequence of accumulated debris in the frontal working gap due to the absence of pressure flushing, supporting the formation of a stationary vortex.…”
Section: Resultsmentioning
confidence: 93%
“…To identify the influence of the tool during groove-grinding with a micro-tool, the edge radius of the tool was analyzed. In EDM, the current was concentrated in a sharp part such as an edge during machining [27], and resulted in the rounding of the edge. If the discharge energy is reduced using a condenser with a small capacitance, sharper edges can be obtained with a smaller energy.…”
Section: Machining Characteristics Of Zirconiamentioning
confidence: 99%
“…Electric Discharge Machine (EDM) is a well-known and advanced process used to machine high precision dies, molds, and various other parts with complex features and high aspect ratio [1].…”
Section: Introductionmentioning
confidence: 99%